An Intervening Maṣlaḥah on Influencing Reward and Punishment for Employee’s Performance: A Study at Warung Spesial Sambal Yogyakarta - bin Lahuri, Setiawan; Almas, Gafita; Zuhroh, Ainun Amalia (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2023)
This study aims to investigate the influence of reward and punishment on employee performance, with maṣlaḥah—an Islamic concept of public benefit—as a mediating variable, based on empirical evidence from Waroeng Spesial Sambal in Yogyakarta. Employing a quantitative research design with Partial Least Squares Structural Equation Modeling (PLS-SEM), the findings demonstrate that both reward and punishment significantly enhance employee performance, directly and indirectly through maṣlaḥah. The construct of maṣlaḥah acts as a critical intervening variable, reinforcing the ethical alignment of organizational behavior with Islamic principles. The results not only validate the efficacy of integrating Islamic ethical frameworks into performance management systems but also reveal maṣlaḥah’s robust mediating effect—suggesting a culturally grounded approach to human resource development. This study offers theoretical advancement by operationalizing maṣlaḥah within a modern organizational context, thereby enriching the literature on Islamic behavioral economics and management. Future research could extend this model across diverse sectors and cultural settings to evaluate the universality and adaptability of maṣlaḥah-oriented performance models in Muslim and non-Muslim work environments.